The Contribution of Islamic Ethics Towards Ethical Accounting Practices (Issues in Social and Environmental Accounting (ISEA), 2011)
The professional ethics of accountants is an important issue directly relating to the integrity of the profession and its ability to secure the public trust. The fraudulent activities in accounting field indicate the failure of accounting education as the beginning stage of the practice. It is perceived that those happen due to deficiency of moral values inserted in the education level. Inevitably, education system is alleged as the main cause of the problem. Accounting education seeks for moral values to generate ethical accountants as part of society. Accordingly, the visibility of ethics education in accounting programs may initiate the development of morality and also increase public confidence in the profession. However, the efforts to integrate ethical values in educational system will not work well if there are no moral commitments implanted in the individuals.  Islam with its divine values plays the notable role to embed cognitive ethical values.  It emphasizes on the unity of God, the accountability to God and the concept of maslahah (public benefits) to be the foundations of ethics. Incorporating Islamic ethics into the system will be a significant contribution towards generating ethical accounting education. This paper attempts to elucidate how the Islamic ethics contribute its role towards ethical accountants as the products of accounting education.